Powers of Tau Proofs

Here’s a starting point for the proofs: https://github.com/a16z/evm-powers-of-tau/blob/master/techreport/main.pdf.

You have $P_{1, j - 1}, P_{2, j - 1}, \ldots, P_{n, j - 1}; P_{+, j - 1}$.

Participant generates $r \xleftarrow{R} \mathbb{F}_p^*$, and publishes $P_{1, j}, P_{2, j}, \ldots; P_{+, j}$. This should satisfy: $$ \begin{aligned} P_{1, j} &= r \cdot P_{1, j - 1}\cr P_{2, j} &= r^2 \cdot P_{2, j - 1}\cr &\ \vdots\cr P_{+, j} &= r \cdot P_{+, j - 1}\cr \end{aligned} $$

The following properties need to be proved:

  1. The prover knows $r$
  2. The prover correctly used $r$, or at least, $P_{i, j}$ consist of a valid powers of tau setup, assuming the $P_{i, j-1}$ did.
  3. $r \neq 0$

The protocol above does 2. with pairings.

Using Maurer Proofs

c.f. my blog post on Maurer proofs

As a starting point, consider the following toy relation:

$$ \begin{aligned} &\{(A, B, G; a, b)\ |\cr &\quad a \cdot G = A\cr &\quad b \cdot G = B\cr &\quad b = a^2\cr &\}\cr \end{aligned} $$

The tricky aspect is the $b = a^2$ part. The rest can be done with a Maurer proof.

One way around this is to tweak the relation slightly:

$$ \begin{aligned} &\{(A, B, G; a, b)\ |\cr &\quad a \cdot G = A\cr &\quad a \cdot A = B\cr &\quad b \cdot G = B\cr &\}\cr \end{aligned} $$

Because $b = a^2$, we have $a \cdot A = a^2 \cdot G = b \cdot G = B$, so this relation is equivalent. Notice also that this relation is captured by the homomorphism:

$$ \varphi(a, b) := (a \cdot G, a \cdot A, b \cdot G) $$

A Maurer proof will work, wherein you check that $\varphi(a, b) = (A, B, B)$

We can extend this to the degree $3$ case as well:

$$ \begin{aligned} &\{(A, B, C, G; a, b, c)\ |\cr &\quad a \cdot G = A\cr &\quad b \cdot G = B\cr &\quad c \cdot G = C\cr &\quad b = a^2\cr &\quad c = a^3\cr &\}\cr \end{aligned} $$

this time, we use the homomorphism:

$$ \varphi(a, b, c) := (a \cdot G, a \cdot A, b \cdot G, a \cdot B, c \cdot G) $$

with expected output $(A, B, B, C, C)$.

Tau Proof

The relation you want to prove is:

$$ \{(P_{i, j}, P_{i, j - 1}; r)\ |\ r^i \cdot P_{i, j - 1} = P_{i, j}\} $$

(taking the convention $\tau^+ = \tau$)

If you had a vector $\bold{r}$ such that $\bold{r}_i = r^i$, then you could just use a standard Maurer proof here. The issue with that is that you need to enforce a specific relation between the vector elements.

We can use the proof we developed in the previous section to get around this restriction though.

We publish $\bold{R} := \bold{r} \cdot G$, and then create a proof for the following relation:

$$ \begin{aligned} &\{(P_{i, j}, P_{i, j - 1}, \bold{R}; \bold{r})\ |\cr &\quad \forall i \in [n - 1].\ \bold{r}_1 \cdot \bold{R}_i = \bold{R}_{i + 1}\cr &\quad \forall i \in [n].\ \bold{r}_i \cdot G = \bold{R}_{i}\cr &\quad \forall i \in [n].\ \bold{r}_i \cdot P_{i, j - 1} = P_{i, j}\cr &\}\cr \end{aligned} $$

This can be done via a Maurer proof for the following homomorphism:

$$ \varphi(\bold{r}) := ([\bold{r}_i \cdot \bold{R}_i], [\bold{r}_i \cdot P_{i, j - 1}]) $$

With the expected output being:

$$ (\bold{R}_{i \geq 2}, [P_{i, j}]) $$

The vector $\bold{r}$ has to be initialized to the powers of $r$.